Estradiol stimulates vasodilatory and metabolic pathways in cultured human endothelial cells. - Agua Sobrino (Public Library of Science (PLoS), 2009)
Vascular effects of estradiol are being investigated because there are controversies among clinical and experimental studies. DNA microarrays were used to investigate global gene expression patterns in cultured human umbilical vein endothelial cells (HUVEC) exposed to 1 nmol/L estradiol for 24 hours. When compared to control, 187 genes were identified as differentially expressed with 1.9-fold change threshold. Supervised principal component analysis and hierarchical cluster analysis revealed the differences between control and estradiol-treated samples. Physiological concentrations of estradiol are sufficient to elicit significant changes in HUVEC gene expression. Notch signaling, actin cytoskeleton signaling, pentose phosphate pathway, axonal guidance signaling and integrin signaling were the top-five canonical pathways significantly regulated by estrogen. A total of 26 regulatory networks were identified as estrogen responsive. Microarray data were confirmed by quantitative RT-PCR in cardiovascular meaning genes; cyclooxygenase (COX)1, dimethylarginine dimethylaminohydrolase (DDAH)2, phospholipase A2 group IV (PLA2G4) B, and 7-dehydrocholesterol reductase were up-regulated by estradiol in a dose-dependent and estrogen receptor-dependent way, whereas COX2, DDAH1 and PLA2G4A remained unaltered. Moreover, estradiol-induced COX1 gene expression resulted in increased COX1 protein content and enhanced prostacyclin production. DDAH2 protein content was also increased, which in turn decreased asymmetric dimethylarginine concentration and increased NO release. All stimulated effects of estradiol on gene and protein expression were estrogen receptor-dependent, since were abolished in the presence of the estrogen receptor antagonist ICI 182780. This study identifies new vascular mechanisms of action by which estradiol may contribute to a wide range of biological processes.